Proportional Feedback Control of Energy Intake during Obesity Pharmacotherapy - Hall, Kevin D. (Obesity (Silver Spring), 2017)
OBJECTIVE: Obesity pharmacotherapies result in an exponential time course for energy intake whereby large early decreases dissipate over time. This pattern of declining drug efficacy to decrease energy intake results in a weight loss plateau within approximately one year. We aimed to elucidate the physiology underlying the exponential decay of drug effects on energy intake. METHODS: We examined the placebo-subtracted energy intake time courses during long-term obesity pharmacotherapy trials for 14 different drugs or drug combinations within the theoretical framework of a proportional feedback control system regulating human body weight. RESULTS: Assuming each obesity drug had a relatively constant effect on average energy intake and did not affect other model parameters, our model correctly predicted that long-term placebo-subtracted energy intake was linearly related to early reductions in energy intake according to a pre-specified equation with no free parameters. The simple model explained about 70% of the variance between drug studies with respect to the long-term effects on energy intake, although a significant proportional bias was evident. CONCLUSIONS: The exponential decay over time of obesity pharmacotherapies to suppress energy intake can be interpreted as a relatively constant effect of each drug superimposed on a physiological feedback control system regulating body weight.